Implementasi Hukum Keluarga Islam Dalam Kehidupan Kontemporer - Dody Wahono Suryo Alam (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
The aim of the research is to describe the implementation of Islamic family law in contemporary life. The research was conducted qualitatively through literature study. Data collection techniques with documentation and data management with data reduction and presentation. The research results show: (1) marriage is the process of uniting two human beings (as a halal couple) which is carried out through a religious court with the principles of freedom to choose a partner, equality, gentleness, deliberation and mutual acceptance. (2) divorce is the process of severing the marriage bond resulting from several problems involving religious courts in the implementation process. The principles that must be considered are making the divorce process more difficult, implementing effective mediation and reviewing divorce procedural law. (3) childcare is a way for parents to develop their children's psychological and physical development by educating, guiding or directing. The principles that need to be considered are maintaining the child's nature, developing the child's potential, providing clear direction and doing it in stages. (4) polygamy is a marriage carried out by one husband with several wives, the implementation of which must pay attention to applicable legal regulations. The principles that must be taken into account are having easy morals, strong faith, sufficient assets, doing this because it is an emergency and must be fair.